Opuntia ficus-indica (L.) Mill. - anticancer properties and phytochemicals: current trends and future perspectives - Wang, Jiao; Rani, Neeraj; Jakhar, Seema; Redhu, Rakesh; Kumar, Sanjiv; Kumar, Sachin; Kumar, Sanjeev; Devi, Bhagwati; Simal-Gandara, Jesus; Shen, Bairong; Singla, Rajeev K. (Frontiers in Plant Science, 2023)
Cancer is a leading cause of mortality worldwide, and conventional cancer therapies such as chemotherapy and radiotherapy often result in undesirable and adverse effects. Natural products have emerged as a promising alternative for cancer treatment, with comparatively fewer side effects reported.Opuntia ficus-indica (L.) Mill., a member of the Cactaceae family, contains a diverse array of phytochemicals, including flavonoids, polyphenols, betalains, and tannins, which have been shown to exhibit potent anticancer properties.Various parts of the Opuntia plant, including the fruits, stems/cladodes, and roots, have demonstrated cytotoxic effects against malignant cell lines in numerous studies. This review comprehensively summarizes the anticancer attributes of the phytochemicals found in Opuntia ficus-indica (L.) Mill., highlighting their potential as natural cancer prevention and treatment agents.Bibliometric metric analysis of PubMed and Scopus-retrieved data using VOSviewer as well as QDA analysis provide further insights and niche to be explored. Most anticancer studies on Opuntia ficus-indica and its purified metabolites are related to colorectal/colon cancer, followed by melanoma and breast cancer. Very little attention has been paid to leukemia, thyroid, endometrial, liver, and prostate cancer, and it could be considered an opportunity for researchers to explore O. ficus-indica and its metabolites against these cancers. The most notable mechanisms expressed and validated in those studies are apoptosis, cell cycle arrest (G0/G1 and G2/M), Bcl-2 modulation, antiproliferative, oxidative stress-mediated mechanisms, and cytochrome c. We have also observed that cladodes and fruits of O. ficus-indica have been more studied than other plant parts, which again opens the opportunity for the researchers to explore. Further, cell line-based studies dominated, and very few studies were related to animal-based experiments. The Zebrafish model is another platform to explore. However, it seems like more in-depth studies are Deleted: wanted 55